2019
DOI: 10.1055/s-0039-1693513
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNA in Liver Regeneration—From Molecular Mechanisms to Clinical Implications

Abstract: The unique ability of the adult liver to regenerate after injury is the basis for efficient surgical resection and liver transplantation and provides solutions for the treatment of liver cancer and acute liver failure. Current success in surgical treatments could be enhanced by directed regulation of liver regeneration. A number of small molecules and growth factors have been tested in mice models to improve liver regeneration. Noncoding ribonucleic acids (ncRNA) are less studied regulators of various cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 214 publications
(207 reference statements)
0
7
0
Order By: Relevance
“…As a lot of lncRNA change expression during liver regeneration [ 42 ], we measured LL35 RNA levels after partial hepatectomy [ 26 ] and found its downregulation 2 h after surgery followed by an increase in the RNA level during the liver’s regeneration ( Figure 1 C). In addition, in our previous study we demonstrated ~70% decrease in the LL35 lncRNA level in mouse liver two weeks after the induction of fibrosis with carbon tetrachloride [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…As a lot of lncRNA change expression during liver regeneration [ 42 ], we measured LL35 RNA levels after partial hepatectomy [ 26 ] and found its downregulation 2 h after surgery followed by an increase in the RNA level during the liver’s regeneration ( Figure 1 C). In addition, in our previous study we demonstrated ~70% decrease in the LL35 lncRNA level in mouse liver two weeks after the induction of fibrosis with carbon tetrachloride [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Liver regeneration may occur after partial hepatectomy, liver transplantation, viral infection, IRI or toxic injury. The regeneration process is complex and well-orchestrated (41,42), and it has been widely studied in order to understand the mechanisms that regulate hepatocyte proliferation and survival (43,44). In normal adult mouse liver, mature differentiated hepatocytes are not vegetative and are quiescent.…”
Section: Complement Cascades Are Essential In Liver Recovery and Regementioning
confidence: 99%
“…Parenchymal and mesenchymal cells, as well as several molecules including metabolites and cytokines, participate in this process (Lorente et al, 2020). The process of liver regeneration consists of three stages: the priming phase (0-6 h), proliferation phase (12-72 h), and termination phase (96-168 h) (Sergeeva et al, 2020). Due to high regeneration capacity, a healthy liver can achieve functional compensation within several weeks after 80% of the liver is resected (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%